Hydraulic mining operation at Schow Mine, Glacier Creek, near Nome, July 1906 - Nowell, Frank H., 1864-1950 (1906)
Caption on image: Miocene Ditch Co. hydraulicking on Schow Mine, Glacier Creek, July 14th 1906. Photo by F.H. Nowell, Nome. 4963. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number